Pengaruh Model Pembelajaran Problem Based Learning Berbasis TPACK Terhadap Keterampilan Literasi Pembelajaran IPAS Kelas IV - Utami, Anis Tri; Handayani, Sri; Handini, Oktiana (JURNAL SINEKTIK, 2024)
This research is a type of quantitative research. The number of samples was 27 students of SD Negeri Madyotaman No. 38 Surakarta for the 2022/2023 academic year who were selected through a saturated sampling technique. Data collection techniques include observation, interviews, tests, and documentation. The test was carried out twice, namely pretest and posttest with the aim of determining the improvement of students' science learning literacy skills before and after treatment. Data analysis techniques in the form of hypothesis tests with T-tests using the Paired Sample T-test formula. Data analysis obtained tcount = 13.521 and ttable with dk = (N-1) so (27-1) = 26 with a significance level of 5% which is 1.706. Then tcount > ttable or 13.521 > 1.706 which means Ha is accepted and Ho is rejected. So it was concluded that "There is an influence of the use of TPACK-based Problem Based Learning Learning Model on Class IV science learning literacy skills of SD Negeri Madyotaman No.38 Surakarta for the 2022/2023 academic year" at a significance level of 5%.